ANALISIS PENGARUH ANTARA BUDGET PARTICIPATION TERHADAP BUDGETARY SLACK (Survei pada Manajer Perusahaan Manufaktur di Indonesia) - Kristianto, Djoko - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2009)
ABSTRACT The influence between budgetary participation and budgetary slack is has been examined in several accounting studies with conflicting result. The sample of this research executed with mail survey method. The total 500 of questionnaires have been given to the population of this research, that are the manager of manufactur company in Indonesia, only 97 questionnaires back and ready to analyze. The result of study showed that budgetary participation and budgetary slack significant influence. Keywords : budgetary participation, budgetary slack.